A transparent hot-melt pressure-sensitive adhesive resistant to ultraviolet light and creep and a preparation method thereof

By using specific polymers in fiber bonding adhesives to prepare hot melt pressure-sensitive adhesives, pretreatment and blending modification, the problem of difficult performance balance in the prior art is solved, and the comprehensive performance optimization of fiber bonding adhesives is achieved.

CN118580815BActive Publication Date: 2025-03-18STEADYCHEM (SHANGHAI) CO LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202410771274.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-14
Publication Date
2025-03-18
Estimated Expiration
2044-06-14

AI Technical Summary

Technical Problem

The prior art is difficult to balance transparency, heat resistance, aging and yellowing resistance and creep resistance while ensuring the adhesive performance of optical fibers, and meet the comprehensive performance needs of optical fiber applications.

Method used

The main resin of the hot melt pressure-sensitive adhesive is prepared by using the first polymer (saturated/hydrogenated polymer), the second polymer (hard-segmental structure polymer) and the third polymer (unsaturated non-hydrogenated polymer), and hydrogenated petroleum resin and functional additives are added to improve the overall performance of the adhesive through pretreatment and blending modification.

Benefits of technology

It achieves comprehensive optimization of transparency, low-temperature/room temperature adhesiveness, heat resistance, UV resistance and humidity and heat aging performance, meets various requirements for fiber optic bonding, and improves the application performance and service life of adhesives.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004894120190000031
    Figure BDA0004894120190000031
  • Figure BDA0004894120190000181
    Figure BDA0004894120190000181
  • Figure BDA0004894120190000211
    Figure BDA0004894120190000211
Patent Text Reader

Abstract

The invention discloses a transparent hot-melt pressure-sensitive adhesive resistant to ultraviolet light and creep, which comprises, by weight, 10-90 parts of a main resin, 35-50 parts of a hydrogenated petroleum resin, 7-20 parts of a plasticizer, 0.3-1 parts of an antioxidant, 0.5-3 parts of an anti-aging agent, and 2-10 parts of a tactile enhancer; wherein the main resin comprises 5-35 parts of a first polymer, 0-25 parts of a second polymer, and 5-30 parts of a third polymer; the first polymer comprises one or more of SEBS, SEPS, SEP, SIBS, and APAO; the second polymer comprises one or more of butyl rubber, polyisobutylene, polyisoprene, and polybutadiene; the third polymer comprises one or more of SBS, SIS, and SBR. The hot-melt pressure-sensitive adhesive for optical fiber prepared by the present invention takes into account transparency, heat resistance, aging resistance, yellowing resistance, and creep resistance while ensuring its bonding performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hot melt pressure sensitive adhesives, in particular to a transparent hot melt pressure sensitive adhesive that is resistant to ultraviolet rays and creep, and a preparation method thereof. Background Art

[0002] Optical fiber communication has greatly facilitated people's lives, but traditional optical cables need to be fixed by placing tape or staples on the wall, which not only damages the wall but also is cumbersome to operate. Adhesive bonding is less destructive and relatively simple to operate. Through the selection of adhesives, transparent optical cables, also known as invisible optical cables, can be made. This type of optical cable does not need to be laid through pipes. It is not only beautiful, but can also be quickly and easily installed around skirtings, doors and windows, and decorative strips, meeting home requirements and minimizing disturbance to residents.

[0003] Invisible optical fiber is very popular in the market. By choosing transparent sheath material and transparent pressure-sensitive adhesive, you can get a transparent optical fiber finished product. The optical fiber is pasted on the wall, which is almost invisible, both beautiful and practical. An excellent pressure-sensitive adhesive for optical fiber bonding needs to have good transparency, good low temperature resistance, good high temperature resistance, good adhesion to various substrates, good UV resistance and good environmental reliability. There is a contradictory relationship between these properties that are mutually opposed and cannot be achieved at the same time.

[0004] Invention CN117304869B discloses a flame retardant transparent hot melt pressure-sensitive adhesive and its preparation method and application. The flame retardant transparent hot melt pressure-sensitive adhesive comprises, by weight percentage: 10-70% of a main resin, 10-70% of a tackifying resin, 0.1-5% of an antioxidant, 0-20% of a plasticizer, 10-50% of a solid powder flame retardant, and 0.1-3% of an aging agent. The main resin comprises a polymer elastomer, and the melt index of the polymer elastomer at a temperature of 200°C and a load of 5.0kg is ≥5g / 10min; the particle size of the solid powder flame retardant is <35μm and D50≤20μm; the softening point of the flame retardant transparent hot melt pressure-sensitive adhesive is 80-140°C, and the transparency is ≥50%, and the haze is ≤80%. The application environment of optical fiber usually needs to withstand conditions such as sunlight and high temperature. The unsaturated double bonds in the main resin of this invention are prone to photo-oxidation reaction under the action of ultraviolet rays, causing the resin molecular chain to break or form new chemical bonds, thereby causing the resin to yellow, causing it to lose its original transparency and aesthetic value, and its properties such as bonding strength are also prone to failure as the resin ages.

[0005] Invention CN101805569B discloses a transparent butyl hot melt sealant, whose raw material components and their weight proportions are as follows: butyl rubber 1-20, polyisobutylene 10-80, plasticizer 5-30, tackifier 3-10, softener 3-10, stabilizer 0.1-5, filler 5-30, and adhesion promoter 0.1-5. The invention uses butyl rubber and polyisobutylene of different molecular weights in combination, but since the sealant basically only contains soft segment structure, its wettability is good, which is conducive to improving the strength and construction performance of the transparent butyl hot melt sealant, but the poor heat resistance leads to great restrictions on the application environment.

[0006] Therefore, how to provide a hot-melt pressure-sensitive adhesive that can be used for optical fibers, while ensuring its bonding performance and balancing the transparency, heat resistance, aging and yellowing resistance, and creep resistance, so as to meet the market demand for both performance and aesthetics, is an urgent problem to be solved by technical personnel in this field. Summary of the invention

[0007] In view of the defects existing in the above-mentioned prior art, the present invention provides a transparent hot-melt pressure-sensitive adhesive which is resistant to UV rays and creep, and a preparation method and application thereof, which takes into account transparency, heat resistance, resistance to aging and yellowing, and creep resistance while ensuring its bonding performance, thereby obtaining a transparent hot-melt pressure-sensitive adhesive for optical fiber with stable and excellent comprehensive performance.

[0008] In a first aspect, the present invention provides a transparent hot-melt pressure-sensitive adhesive having UV resistance and creep resistance, comprising the following components in parts by weight:

[0009]

[0010] Wherein, by weight, the main resin includes:

[0011] 5-35 parts of the first polymer

[0012] Second polymer 0-25 parts

[0013] 5-30 parts of the third polymer

[0014] The first polymer includes one or more of styrene-ethylene-butadiene-styrene block copolymer (SEBS), styrene-ethylene / propylene-styrene block copolymer (SEPS), hydrogenated styrene isoprene diblock copolymer (SEP), styrene-polyisobutylene-styrene block copolymer (SIBS), and pressure-sensitive amorphous polyolefin (APAO);

[0015] The second polymer includes one or more of butyl rubber (IIR), polyisobutylene (PIB), polyisoprene (LIR), and polybutadiene (LBR);

[0016] The third polymer includes one or more of styrene-butadiene-styrene block copolymer (SBS), styrene-isoprene-styrene block copolymer (SIS) and styrene-butadiene block copolymer (SBR).

[0017] The first polymer is a saturated / hydrogenated saturated polymer, which basically does not contain unsaturated groups in the molecular chain, so it has excellent UV resistance and good resistance to wet heat aging. However, compared with unhydrogenated rubber or unsaturated rubber (such as SIS), the intermolecular force between the first polymer and the substrate is lower, and the adhesion to the substrate is lower. When the amount is small, it cannot achieve the effect of UV resistance, and when the amount is large, the overall adhesion will be reduced.

[0018] The second polymer is a polymer with basically no hard segment structure. Compared with ordinary rubber (such as SEBS, SIS), this type of polymer basically only contains soft segment structure and no hard segment structure. Therefore, it has good wettability and high adhesion to the substrate. The amount should not be too much, otherwise it will easily significantly reduce the overall heat resistance.

[0019] The third polymer is an unsaturated non-hydrogenated polymer. Compared with hydrogenated rubber (such as SEBS), this type of polymer contains unsaturated double bonds in the molecular chain, and the polymer selected through special structure has higher adhesion to the substrate than hydrogenated polymer. However, the UV resistance is poor. When the dosage is small, the adhesion to the substrate cannot be improved. When the dosage is large, the UV resistance and long-term wet heat aging performance are reduced.

[0020] The second polymer and the third polymer both have better bonding properties than the first polymer, and either one of them can be selected, but it is preferred to use at least the third polymer, or use both of them simultaneously.

[0021] The transparent hot-melt pressure-sensitive adhesive of the present invention has a softening point of 80-150°C; transparency ≥50%, preferably ≥60%, more preferably ≥80%; haze ≤80%, preferably ≤60%, more preferably ≤50%; room-temperature adhesion to the substrate ≥1N / mm, preferably ≥1.2N / mm; room-temperature adhesion to the substrate after UV aging ≥0.4N / mm, preferably ≥0.6N / mm; color difference after UV aging ≤3.5.

[0022] Preferably, the hydrogenated petroleum resin includes one or more of hydrogenated C5 petroleum resin, hydrogenated C5-C9 copolymer petroleum resin, hydrogenated C9 petroleum resin, and styrene series monomer resin;

[0023] The plasticizer comprises at least one of mineral oil and low molecular weight polyisobutylene;

[0024] The antioxidant comprises at least one of antioxidant 1010 and antioxidant 168;

[0025] The anti-aging agent includes at least one of an ultraviolet absorber and a light stabilizer.

[0026] Further preferably, the hydrogenated petroleum resin is a hydrogenated C5C9 copolymer petroleum resin, and the Ring and Ball softening point is greater than 80°C and less than 130°C;

[0027] The plasticizer is naphthenic oil and / or polyisobutylene with a molecular weight lower than 1300;

[0028] The ultraviolet absorber includes one or more of UV326, UV328, and UV-P;

[0029] The light stabilizer is one or more of UV944 and UV622.

[0030] In parts by weight, the main resin includes:

[0031] 10-30 parts of the first polymer

[0032] 5-20 parts of the second polymer

[0033] 10-25 parts of the third polymer,

[0034] The first polymer is selected from at least one of styrene-ethylene-butadiene-styrene block copolymer (SEBS), styrene-ethylene / propylene-styrene block copolymer (SEPS), and pressure-sensitive amorphous polyolefin (APAO);

[0035] Among them, styrene-ethylene-butadiene-styrene block copolymer (SEBS), styrene-ethylene / propylene-styrene block copolymer (SEPS), styrene content ≤ 30%, MI value > 5, 200°C, 5.0kg; cohesive strength of pressure-sensitive amorphous polyolefin (APAO) < 2.5MPa;

[0036] The second polymer has no hard segment structure and a weight average molecular weight Mw ranging from 100,000 to 1.5 million;

[0037] The third polymer has a styrene content of ≤30%, a diblock content of ≥50%, and an MI value of >5, 200° C., 5.0 kg.

[0038] Preferably, the contact enhancer includes at least one of nano calcium carbonate, nano zinc oxide, nano zirconium oxide, nano aluminum oxide, fumed silica, precipitated silica, nano talc, organic bentonite, polyamide wax and phosphate.

[0039] As a contact enhancer in hot melt pressure sensitive adhesives, the main function of fumed silica is to improve the thixotropy of the adhesive, that is, to increase the viscosity in a static state to improve the stability of storage and transportation, and to reduce the viscosity in a shear state to facilitate construction and coating. This characteristic enables the adhesive to adhere better to the substrate when applied, reducing the resistance to application, and preventing sagging when applied on vertical or inclined surfaces, maintaining the uniformity of the coating. At the same time, the addition of a contact enhancer also helps to improve the bonding strength between the adhesive and the substrate, improve storage stability, optimize drying performance, and improve temperature resistance, thereby significantly improving the application performance and service life of the hot melt pressure sensitive adhesive.

[0040] Preferably, the contact enhancer comprises fumed silica loaded with UV326, with a particle size of <25 μm, and the amount of UV326 accounts for 5-20% of the weight of the fumed silica, and comprises the following loading steps:

[0041] (1) adding an aminosilane coupling agent to an organic dispersion of fumed silica to react and obtain a modified silica suspension;

[0042] (2) Add UV326 and a catalyst to the suspension of step (1), and stir the reaction under nitrogen protection to obtain fumed silica loaded with UV326.

[0043] Wherein, in step (1), the aminosilane coupling agent is used in an amount of 3-10% of the mass of the fumed silica, and is selected from one or more of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldiethoxysilane, γ-aminopropylmethyldiethoxysilane, γ-aminopropylmethyldimethoxysilane and γ-aminopropylethoxydimethylsilane.

[0044] When the aminosilane coupling agent reacts with silica particles, one end of the alkoxy group can undergo a water (alcohol) decomposition condensation reaction with the hydroxyl group on the surface of the silica particles and be grafted onto the surface of the silica particles, while the amino group on the other end is retained, which has a high reactivity.

[0045] In step (2), preferably, 5-20% of UV326 by mass of silica and 1-10% of a tertiary amine catalyst are added to the suspension obtained in step (1), and the reaction is stirred under nitrogen protection. When no hydrogen chloride is released, the reaction is filtered, washed and dried to obtain silica with a surface-loaded anti-aging agent.

[0046] Preferably, the third polymer is pre-blended and modified with the UV326-loaded fumed silica, comprising the following steps:

[0047] Add the third polymer, maleic anhydride, and UV326-loaded fumed silica into a kneader or a screw extruder, and react at 140-160° C. for 1-2 hours to obtain a modified third polymer.

[0048] The premixing and modification of the UV326-loaded tactile enhancer and the third polymer with poor UV resistance by maleic anhydride is beneficial to improving the UV resistance of the third polymer, and also helps to improve the mixing uniformity and stability of the tactile enhancer and its load in the main resin, and overall improves the aging resistance of the pressure-sensitive adhesive. The amount of maleic anhydride preferably accounts for 1-5% of the total mass of the third polymer. When using fumed silica to load UV326, other similar or different anti-aging agents can also be used in combination and added to the mixed system by blending.

[0049] Preferably, at least part of the first polymer grafted antioxidant 1010 comprises the following steps:

[0050] (1) dissolving maleic anhydride in an organic solvent to obtain a reserve solution; adding the organic solvent, antioxidant 1010 and catalyst into a reaction container, and stirring to obtain a uniform solution; wherein the molar ratio of maleic anhydride, antioxidant 1010 and catalyst is (1.1-1.3):1:(0.1-0.3);

[0051] (2) Under nitrogen protection, the solution temperature is lowered to -20°C to -5°C, and the reserve solution is dripped into the reaction container to react the antioxidant 1010 with maleic anhydride;

[0052] (3) After the reaction is completed, the temperature of the mixed solution in the reaction container is raised to 0° C. to 15° C., and deionized water is added dropwise to the mixed solution for quenching;

[0053] (4) separating the organic phase after standing, concentrating under reduced pressure, cooling to crystallize, filtering and drying to obtain a reactive antioxidant;

[0054] (5) adding at least a portion of the first polymer to an internal mixer for melting, adding the reactive antioxidant, mixing for 5-10 minutes, and then adding the organic peroxide, mixing for 1-5 minutes to obtain the first polymer grafted with an antioxidant.

[0055] Using 10-50% of the first polymer to pre-react with the antioxidant 1010 is beneficial to improving the dispersibility of the antioxidant in the main resin and improving the overall long-lasting and stable antioxidant performance of the hot melt pressure sensitive adhesive. While using the first polymer to graft the antioxidant 1010, other antioxidants can also be used in combination and added to the mixed system by blending.

[0056] In a second aspect, the present invention further provides a method for preparing the UV-resistant and creep-resistant transparent hot-melt pressure-sensitive adhesive, comprising the following steps:

[0057] S1, adding a first polymer, a hydrogenated petroleum resin, a plasticizer, an antioxidant and an optional second polymer into a preheated reaction device, and stirring thoroughly to obtain a premix;

[0058] S2. Add an anti-aging agent, a catalytic enhancer and a third polymer to the premix, stir thoroughly, and evacuate to obtain a transparent hot-melt pressure-sensitive adhesive product that is UV-resistant and creep-resistant.

[0059] Preferably, the antioxidant comprises antioxidant 1010, and 10-50% of the first polymer is used for pre-graft reaction with antioxidant 1010.

[0060] Preferably, the contact enhancer includes fumed silica loaded with UV326, the UV326 used for loading accounts for 30-60% of the total amount of the anti-aging agent, and the third polymer is pre-blended and modified with the fumed silica loaded with UV326.

[0061] In a third aspect, the present invention provides an application of the UV-resistant and creep-resistant transparent hot-melt pressure-sensitive adhesive in optical fiber bonding.

[0062] The present invention has the following beneficial effects:

[0063] (1) The present invention uses a first polymer (saturated / hydrogenated polymer), a third polymer (unsaturated non-hydrogenated polymer), and an optional second polymer (polymer without a hard segment structure) to prepare the main resin component of the hot melt pressure-sensitive adhesive, and adds hydrogenated petroleum resin to improve the wettability of the colloid and other functional additives, thereby enhancing its adhesion to various surfaces, thereby preparing a hot melt pressure-sensitive adhesive with excellent comprehensive properties such as transparency, low-temperature / normal-temperature adhesion, heat resistance, UV resistance, and wet-heat aging performance, which meets all requirements for optical fiber bonding.

[0064] (2) The present invention pre-treats the first polymer and the third polymer according to their characteristics. Part of the first polymer is grafted with an antioxidant through maleic anhydride, and the antioxidant structure is bonded to the polymer chain, which can effectively reduce the mobility, volatility, and resistance to extraction of ordinary antioxidant small molecules, so that the antioxidant can play an antioxidant role for a long time; the ultraviolet absorber is loaded on the surface of the gas phase silica, and the gas phase silica loaded with the ultraviolet absorber, maleic anhydride and the third polymer are pre-blended and modified, which solves the shortcomings of uneven distribution, resistance to extraction, easy migration and easy loss of small molecule ultraviolet absorbers on the one hand, and on the other hand, it can improve the aging resistance of the unsaturated third polymer during use, and at the same time improve the comprehensive mechanical properties and environmental aging resistance of the polymer material. DETAILED DESCRIPTION

[0065] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with specific implementation methods. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0066] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings, and "multiple" generally includes at least two.

[0067] It should also be noted that the term "includes", "comprising" or any other variation thereof is intended to cover non-exclusive inclusion, so that a commodity or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such commodity or device. In the absence of more restrictions, the elements defined by the sentence "comprising a ..." do not exclude the existence of other identical elements in the commodity or device including the elements.

[0068] A transparent hot-melt pressure-sensitive adhesive that is UV-resistant and creep-resistant, comprising the following components in parts by weight:

[0069] 1. 10-90 parts of main resin, specifically including:

[0070] 1.1 5-35 parts of the first polymer, preferably 10-30 parts;

[0071] The first polymer includes one or more of styrene-ethylene-butadiene-styrene block copolymer (SEBS), styrene-ethylene / propylene-styrene block copolymer (SEPS), hydrogenated styrene isoprene diblock copolymer (SEP), styrene-polyisobutylene-styrene block copolymer (SIBS), and pressure-sensitive amorphous polyolefin (APAO), preferably at least one of styrene-ethylene-butadiene-styrene block copolymer (SEBS), styrene-ethylene / propylene-styrene block copolymer (SEPS), and pressure-sensitive amorphous polyolefin (APAO);

[0072] Among them, at least one of styrene-ethylene-butadiene-styrene copolymer (SEBS) and styrene-ethylene / propylene-styrene block copolymer (SEPS) is preferred, with a styrene content of ≤30%, an MI value of >5, 200°C, 5.0kg; and a cohesive strength of the pressure-sensitive amorphous polyolefin (APAO) of <2.5MPa;

[0073] More preferably, 10-50% of the first polymer is pre-grafted with an antioxidant 1010, comprising the following steps:

[0074] (1) dissolving maleic anhydride in an organic solvent to obtain a reserve solution; adding the organic solvent, antioxidant 1010 and catalyst into a reaction container and stirring to obtain a uniform solution; wherein the organic solvent is chloroform or toluene, the catalyst is 4-dimethylaminopyridine, and the molar ratio of maleic anhydride, antioxidant 1010 and catalyst is (1.1-1.3):1:(0.1-0.3);

[0075] (2) Under nitrogen protection, the solution temperature is lowered to -20°C to -5°C, and the reserve solution is dripped into the reaction container to react the antioxidant 1010 with maleic anhydride;

[0076] (3) After the reaction is completed, the temperature of the mixed solution in the reaction container is raised to 0° C. to 15° C., and deionized water is added dropwise to the mixed solution for quenching;

[0077] (4) separating the organic phase after standing, concentrating under reduced pressure, cooling to crystallize, filtering and drying to obtain a reactive antioxidant;

[0078] (5) adding the first polymer to an internal mixer to melt, adding the reactive antioxidant, mixing for 5-10 minutes, and then adding the organic peroxide, mixing for 1-5 minutes to obtain the first polymer grafted with an antioxidant.

[0079] The amount of antioxidant 1010 used in the pre-grafting reaction is 0.1-3% of the weight of the first polymer participating in the reaction.

[0080] The organic peroxide comprises a dialkyl peroxide initiator, and the dialkyl peroxide initiator is selected from one or more of the group consisting of bis(tert-butyl peroxyisopropyl)benzene, 2,5-dimethyl-2,5-di-tert-butyl peroxyhexane, diisopropylbenzene peroxide, tert-butyl peroxyisopropylbenzene and di-tert-butyl peroxide. The amount of the organic peroxide is 0.05-1% of the weight of the first polymer participating in the reaction, preferably 0.1-0.5%.

[0081] 1.2 0-25 parts of the second polymer, preferably 5-20 parts;

[0082] The second polymer includes one or more of butyl rubber (IIR), polyisobutylene (PIB), polyisoprene (LIR), and polybutadiene (LBR); preferably has no hard segment structure, and has a weight average molecular weight Mw between 100,000 and 1.5 million;

[0083] 1.3 5-30 parts of the third polymer, preferably 10-25 parts;

[0084] The third polymer includes one or more of styrene-butadiene-styrene block copolymer (SBS), styrene-isoprene-styrene block copolymer (SIS) and styrene-butadiene block copolymer (SBR); preferably, the styrene content is ≤30%, the diblock content is ≥50%, and the MI value is >5, 200°C, 5.0kg.

[0085] Preferably, the third polymer is pre-blended with a catalytic enhancer loaded with an ultraviolet absorber for modification, wherein the catalytic enhancer loaded with an ultraviolet absorber is fumed silica loaded with UV326, comprising the following steps: adding the third polymer, maleic anhydride, and fumed silica loaded with UV326 to a kneader or a screw extruder, and reacting at 140-160° C. for 1-2 hours to obtain a modified third polymer.

[0086] 2. 35-50 parts of hydrogenated petroleum resin, including one or more of hydrogenated C5 petroleum resin, hydrogenated C5C9 copolymer petroleum resin, hydrogenated C9 petroleum resin, and styrene series monomer resin; the hydrogenated petroleum resin is preferably hydrogenated C5C9 copolymer petroleum resin, with a Ring and Ball softening point greater than 80°C and less than 130°C;

[0087] 3. Other additives:

[0088] 3.1 7-20 parts of a plasticizer, comprising at least one of mineral oil and low molecular weight polyisobutylene; the plasticizer is preferably naphthenic oil, and / or polyisobutylene with a molecular weight lower than 1300;

[0089] 3.2 0.3-1 part of an antioxidant, comprising at least one of antioxidant 1010 and antioxidant 168; the antioxidant preferably comprises antioxidant 1010 and is pre-grafted with a portion of the first polymer;

[0090] 3.3 0.5-3 parts of anti-aging agent, including at least one of ultraviolet absorber and light stabilizer, the ultraviolet absorber includes one or more of UV326, UV328, UV-P, preferably includes UV326; the light stabilizer is one or more of UV944 and UV622;

[0091] 3.4 2-10 parts of a contact enhancer, including at least one of nano calcium carbonate, nano zinc oxide, nano zirconium oxide, nano aluminum oxide, fumed silica, precipitated silica, nano talc, organic bentonite, polyamide wax and phosphate. Preferably, the contact enhancer is fumed silica, more preferably fumed silica loaded with UV326, with a particle size of <25 μm, and the amount of UV326 used for loading accounts for 5-20% of the weight of the fumed silica. The preparation method comprises:

[0092] (1) Adding fumed silica particles into an organic solvent and stirring to form a silica dispersion:

[0093] (2) adding 3-10% of the mass of silica to the silica dispersion, stirring and reacting under reflux of an organic solvent to obtain a silica suspension modified by the aminosilane coupling agent;

[0094] (3) Add 5-20% of UV326 by mass of silica and 1-10% of tertiary amine catalyst to the suspension obtained in step (2), stir and react under nitrogen protection, filter, wash and dry until no hydrogen chloride is released, and obtain silica with surface-loaded anti-aging agent.

[0095] Wherein, the aminosilane coupling agent is selected from one or more of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldiethoxysilane, γ-aminopropylmethyldiethoxysilane, γ-aminopropylmethyldimethoxysilane and γ-aminopropylethoxydimethylsilane.

[0096] The organic solvent is selected from one or more of benzene, toluene, xylene, N,N-dimethylformamide, N,N-dimethylacetamide, dichloromethane and chloroform.

[0097] The tertiary amine catalyst is selected from one or more of pyridine, triethylamine, trimethylamine, quinoline, picoline and xylidine.

[0098] According to the selection and pretreatment of the aforementioned components, the preparation method of the UV-resistant, creep-resistant transparent hot-melt pressure-sensitive adhesive of the present invention comprises the following steps:

[0099] S1, adding a first polymer, a hydrogenated petroleum resin, a plasticizer, an antioxidant and an optional second polymer into a preheated reaction device, and stirring them thoroughly to obtain a premix;

[0100] S2. Add an anti-aging agent, a catalytic enhancer and a third polymer to the premix, stir thoroughly, and evacuate to obtain a transparent hot-melt pressure-sensitive adhesive product that is UV-resistant and creep-resistant.

[0101] Corresponding to the above-mentioned material composition, the antioxidant at least includes antioxidant 1010, and 10-50% of the first polymer is used for pre-grafting reaction with antioxidant 1010; the amount of antioxidant 1010 used for pre-grafting reaction is 0.1-3% of the weight of the first polymer participating in the reaction, preferably 0.5-1.5%, and the remaining antioxidants (including antioxidant 1010) can be added and mixed in step S1;

[0102] The anti-aging agent includes at least UV326, and the catalytic enhancer includes at least fumed silica loaded with UV326. A third polymer and the fumed silica loaded with UV326 are pre-blended and modified, and then the modified third polymer and the optional remaining anti-aging agents and catalytic enhancers are added to the premix in step S2.

[0103] Preparation Example A

[0104] The main resin of this preparation example uses only the first polymer and the third polymer, and involves Examples A1-A7 and Comparative Examples D1-D2.

[0105] Embodiment A1-A4:

[0106] UV-resistant, creep-resistant, transparent hot-melt pressure-sensitive adhesive samples were prepared by the following method:

[0107] S1. Raise the temperature of the stirring device to 150° C., then add SEBS rubber (Kraton G 1657), pressure-sensitive amorphous polyolefin (Aerafin 180), hydrogenated petroleum resin, plasticizer, antioxidant (antioxidant 1010) thereto, and stir thoroughly to obtain a premix;

[0108] S2. Add anti-aging agent (UV326), tactile enhancer and SIS rubber (Vector4114) to the premix, stir thoroughly until the materials are evenly mixed, and vacuum to remove bubbles to obtain hot melt pressure-sensitive adhesive filling material.

[0109] Embodiment A5:

[0110] This embodiment differs from embodiment A1 in that, before step S2, a catalytic enhancer (fumed silica) is used to load 45% of an anti-aging agent (UV326), SIS rubber and the fumed silica loaded with UV326 are pre-blended and modified to obtain a modified SIS rubber, and then the modified SIS rubber and the remaining anti-aging agent are added to the premix of step S1, specifically comprising:

[0111] (1) Adding fumed silica particles into an organic solvent, toluene, and stirring to form a silica dispersion:

[0112] (2) adding γ-aminopropyltrimethoxysilane coupling agent at 5% by mass of silica to the silica dispersion, stirring and reacting under toluene reflux to obtain a silica suspension modified by aminosilane coupling agent;

[0113] (3) adding 15% UV326 by mass of silica and 5% tertiary amine catalyst to the suspension obtained in step (2), stirring and reacting under nitrogen protection, filtering, washing and drying until no hydrogen chloride is released to obtain silica with UV326 loaded on the surface;

[0114] (4) Add SIS rubber, maleic anhydride, and UV326-loaded fumed silica to a kneader or screw extruder, and react at 150±5° C. for 1.5 h to obtain a modified third polymer. The amount of maleic anhydride used accounts for 2% of the total mass of the third polymer.

[0115] Embodiment A6:

[0116] This embodiment differs from embodiment A1 in that 40% of SEBS rubber (first polymer) and antioxidant (antioxidant 1010) are pre-reacted and then used together in step S1. The pre-reaction includes the following steps:

[0117] (1) dissolving maleic anhydride in an organic solvent to obtain a reserve solution; adding the organic solvent, antioxidant 1010 and catalyst into a reaction container and stirring to obtain a uniform solution; wherein the organic solvent is chloroform, the catalyst is 4-dimethylaminopyridine, and the molar ratio of maleic anhydride, antioxidant 1010 and catalyst is 1.2:1:0.2;

[0118] (2) Under nitrogen protection, the solution temperature was lowered to -10±2°C, and the reserve solution was dripped into the reaction container to allow the antioxidant 1010 and maleic anhydride to react;

[0119] (3) After the reaction is completed, the temperature of the mixed solution in the reaction container is raised to 10±2°C, and deionized water is added dropwise to the mixed solution for quenching;

[0120] (4) separating the organic phase after standing, concentrating under reduced pressure, cooling to crystallize, filtering and drying to obtain a reactive antioxidant;

[0121] (5) Add SEBS rubber to an internal mixer to melt, add the reactive antioxidant, mix for 8 minutes, then add diisopropylbenzene peroxide, mix for 3 minutes, and obtain SEBS rubber grafted with antioxidant. The amount of grafted antioxidant 1010 accounts for about 1.25% of the amount of SEBS rubber involved in the reaction, and the remaining antioxidants can be blended.

[0122] Embodiment A7:

[0123] On the basis of Example A1, with reference to the manner of Examples A5 and A6, the first polymer and the third polymer were subjected to a modification pre-reaction.

[0124] Comparative Examples D1-D2:

[0125] The main difference between the comparative example and Example A1 is that no catalytic enhancer is added, the other material compositions are slightly adjusted, and the preparation process is the same.

[0126] The specific ingredients and their proportions of Examples A1-A7 and Comparative Examples D1-D2 are shown in Table 1 (unit / part):

[0127] Table 1

[0128]

[0129] Preparation Example B:

[0130] The main resin of this preparation example uses a first polymer, a second polymer and a third polymer, and involves Examples B1-B8 and Comparative Examples D3-D4.

[0131] Embodiment B1-B5:

[0132] UV-resistant, creep-resistant, transparent hot-melt pressure-sensitive adhesive samples were prepared by the following method:

[0133] S1. Raise the temperature of the stirring device to 150° C., then add SEPS rubber (Septon 2063) and / or pressure-sensitive amorphous polyolefin (Vestoplast 751), butyl rubber, hydrogenated petroleum resin, plasticizer, antioxidant (antioxidant 1010) and optional polyisobutylene thereto, and stir thoroughly to obtain a premix;

[0134] S2. Add anti-aging agent (UV326), catalytic enhancer and SBS rubber (Globalprene 3522) to the premix, stir thoroughly until the materials are evenly mixed, and vacuum to remove bubbles to obtain hot melt pressure-sensitive adhesive filling material.

[0135] Embodiment B6:

[0136] This embodiment differs from embodiment B1 in that, before step S2, a catalytic enhancer (fumed silica) is used to load an anti-aging agent (UV326), SBS rubber and the fumed silica loaded with UV326 are pre-blended and modified to obtain a modified SBS rubber, and then the modified SBS rubber is added to the premix of step S1, specifically comprising:

[0137] (1) Adding fumed silica particles into an organic solvent, toluene, and stirring to form a silica dispersion:

[0138] (2) adding γ-aminopropyltrimethoxysilane coupling agent at 5% by mass of silica to the silica dispersion, stirring and reacting under toluene reflux to obtain a silica suspension modified by aminosilane coupling agent;

[0139] (3) adding 20% ​​UV326 by mass of silica and 5% tertiary amine catalyst to the suspension obtained in step (2), stirring and reacting under nitrogen protection, filtering, washing and drying until no hydrogen chloride is released to obtain silica with UV326 loaded on the surface;

[0140] (4) Add SBS rubber, maleic anhydride, and UV326-loaded fumed silica to a kneader or screw extruder, and react at 150±5° C. for 1.5 h to obtain a modified third polymer. The amount of maleic anhydride used accounts for 2% of the total mass of the third polymer.

[0141] Example B7:

[0142] This embodiment differs from embodiment B1 in that 40% of the SEPS rubber (first polymer) and the antioxidant (antioxidant 1010) are pre-reacted and then used together in step S1. The pre-reaction includes the following steps:

[0143] (1) dissolving maleic anhydride in an organic solvent to obtain a reserve solution; adding the organic solvent, antioxidant 1010 and catalyst into a reaction container and stirring to obtain a uniform solution; wherein the organic solvent is chloroform, the catalyst is 4-dimethylaminopyridine, and the molar ratio of maleic anhydride, antioxidant 1010 and catalyst is 1.2:1:0.2;

[0144] (2) Under nitrogen protection, the solution temperature was lowered to -10±2°C, and the reserve solution was dripped into the reaction container to allow the antioxidant 1010 and maleic anhydride to react;

[0145] (3) After the reaction is completed, the temperature of the mixed solution in the reaction container is raised to 10±2°C, and deionized water is added dropwise to the mixed solution for quenching;

[0146] (4) separating the organic phase after standing, concentrating under reduced pressure, cooling to crystallize, filtering and drying to obtain a reactive antioxidant;

[0147] (5) Add the SEPS rubber to an internal mixer to melt, add the reactive antioxidant, mix for 8 minutes, then add diisopropylbenzene peroxide, mix for 3 minutes, and obtain the SEPS rubber grafted with the antioxidant. The amount of the grafted antioxidant 1010 accounts for about 1.5% of the amount of the SEBS rubber involved in the reaction, and the remaining antioxidants can be blended.

[0148] Embodiment B8:

[0149] On the basis of Example B1, with reference to the manner of Examples B6 and B7, the first polymer and the third polymer were subjected to a modification pre-reaction.

[0150] Comparative Example D3:

[0151] The main difference between this comparative example and Example B1 is that an excess amount of the third polymer is used, but an insufficient amount of the hydrogenated petroleum resin is used. The other preparation processes are the same.

[0152] Comparative Example D4:

[0153] The main difference between this comparative example and Example B1 is that no catalytic enhancer is added, and the other preparation processes are the same.

[0154] The specific ingredients and proportions of Examples B1-B8 and Comparative Examples D3-D4 are shown in Table 2 (unit / part):

[0155] Table 2

[0156]

[0157] Sources of commodities in the table:

[0158] Kraton G 1657 is a SEBS rubber purchased from Kraton Polymers Co., Ltd., with a styrene content of 13%, a diblock content of 30%, a melt index of 8, 200°C, and 5.0 kg.

[0159] Aerafin 180 is a polyolefin purchased from Syntema, with a ring and globe softening point of 120°C.

[0160] Vector 4114 is SIS rubber purchased from Taiwan Rubber, with a styrene content of 15% by weight and a diblock content of 42% by weight.

[0161] Escorez 5320 is a hydrogenated petroleum resin purchased from ExxonMobil, with a ring and globe softening point of 124°C.

[0162] KN 4010 is naphthenic oil purchased from Xinjiang Karamay Co., Ltd.

[0163] Irganox 1010 is an antioxidant purchased from BASF.

[0164] Tinuvin 326 is an ultraviolet absorber purchased from BASF, referred to as UV326.

[0165] TS 620 is a hydrophobic fumed silica available from Cabot.

[0166] HJ-306 is active nano calcium carbonate purchased from Shanghai Huijingya Nano New Materials Co., Ltd., with a particle size of 100 nm.

[0167] Vestoplast 751 is a polyolefin purchased from Evonik, with a ring and globe softening point of 100°C.

[0168] Septon 2063 is a SEPS rubber purchased from Kuraray, and the diblock content accounts for 13% by weight.

[0169] ExxonButyl 268 is a butyl rubber purchased from ExxonMobil, with a Mooney viscosity of 50.

[0170] HB-80 is polyisobutylene purchased from Zhejiang Xinhui New Materials Co., Ltd., with a Mw of about 800,000.

[0171] Globalprene 3522 is an SBS rubber purchased from Lee Chang Jung Chemical, with a styrene content of 23% by weight and a diblock content of 78% by weight.

[0172] Plastolyn 240 is a monomer petroleum resin purchased from Syntema, with a ring and globe softening point of 120°C.

[0173] TPC1105 is a polyisobutylene plasticizer purchased from TPC Company in the United States, with a Mw of about 1050.

[0174] Test Method

[0175] 1. The melt index test conditions are: the temperature is 200°C and the load is 5.0 kg.

[0176] 2. Softening point test method: melt the hot melt pressure sensitive adhesive sample into a ring mold, let it stand for 24 hours, and then use a softening point tester to test the softening point of the material. The test method refers to GB / T15332-1994.

[0177] 3. Haze and transparency test method: At 170℃, use a knife coater to coat the hot melt pressure sensitive adhesive sample on the release surface of a 50μm transparent PET release film, control the film thickness to 300μm, and attach a 50μm thick PET release film to the surface. Then use a haze tester to test the haze and transparency of the pressure sensitive adhesive sample. The test method refers to the test method in GB / T2410-2008 Transparent Plastic Transmittance and Haze Determination.

[0178] 4. Test method for the room-temperature adhesion of PVC wallpaper: Coat the hot-melt pressure-sensitive adhesive sample on the optical cable (width 3.2mm, thickness 1.3mm, length 100mm), control the width of the hot-melt pressure-sensitive adhesive layer to 3.2mm, the thickness to 0.4mm, and the length to 100mm, and then stick the optical cable coated with the hot-melt pressure-sensitive adhesive sample on the PVC wallpaper (width 100mm, thickness 5mm, length 200mm). After placing it at 23°C for 4h, test the 90° peeling force, measure it 4 times in parallel, and take the average value.

[0179] 5. Low temperature stability test method: The sample preparation process is the same as 4. After sample preparation, place the sample in a 5°C walk-in refrigerator for 4 hours, test the 90° peel strength, measure 4 times in parallel, and take the average value.

[0180] 6. Test method for wet heat aging performance: The sample preparation process is the same as 4. After sample preparation, place the sample in an oven at a temperature of 70°C and a humidity of 90% for 500 hours. After taking it out, let it stand at room temperature for 24 hours. Test the 90° peel force at room temperature. Measure it 4 times in parallel and take the average value.

[0181] 7. Creep resistance test method: Apply the hot melt pressure sensitive adhesive sample on the optical cable, attach a release film on the surface and roll it up. Control the width of the hot melt pressure sensitive adhesive layer to be 3.2mm, the thickness to be 0.4mm, and the length to be 20m. Place the entire roll of cable at room temperature for 24h, and then place it in a 70℃ oven for 48h. After taking it out, test the peeling force between the cables. If the peeling force is greater than 2.5N, it is judged to be adhesion, otherwise there is no adhesion.

[0182] 8. Test method for UV resistance: The sample preparation process is the same as 4. Apply the hot melt pressure sensitive adhesive to the cable, then bond it to the PVC wallpaper, place it in an environmental chamber for aging, observe whether the adhesive layer cracks after 1000 hours, and test the adhesion to the PVC wallpaper. The aging standard refers to ISO4892-2.

[0183] Test Results

[0184] The test results of Examples A1-A7 of Preparation Example A and Comparative Examples D1-D2 are shown in Table 3:

[0185] Table 3

[0186]

[0187]

[0188] The test results of Examples B1-B8 and Comparative Examples D3-D4 of Preparation Example B are shown in Table 4:

[0189] Table 4

[0190]

[0191] A1-A4 can prepare samples that meet the requirements. A5-A7 are all based on polymer-modified formulas. The mixing of each component is more efficient, and its wet heat aging performance and UV resistance are improved. D1 and D2 do not use a contact enhancer. D1 has a high softening point, which ensures no adhesion at high temperatures, but due to excessive cohesion and poor wetting ability, its room temperature and low temperature adhesion is very weak. D2 uses a large amount of SIS rubber. Since SIS rubber contains unsaturated double bonds and has poor UV resistance, it causes cracking of the adhesive layer after UV testing, and the color difference is relatively large. At the same time, the adhesion is significantly reduced after UV aging. D2 retains an appropriate softening point, but due to the lack of a contact enhancer, it adheres at high temperatures.

[0192] B1-B5 can also prepare samples that meet the requirements by using different combinations. The wet heat aging performance and UV resistance of the modified formula of B6-B8 are improved. Although D3 uses a catalytic enhancer, the content of the third polymer SBS rubber is too high, the double bond content in the system is relatively high, and the UV resistance is poor, resulting in large color difference after UV testing and cracking of the adhesive layer. D4 has adhesion at high temperature without adding a catalytic enhancer.

[0193] Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they are aware of the basic creative concepts. Therefore, the present invention is intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention. Obviously, those skilled in the art may make various changes and modifications to the present invention without departing from the spirit and scope of the present invention.

Claims

1. A transparent hot melt pressure-sensitive adhesive that is UV-resistant and creep-resistant, characterized in that: In parts by weight, it includes the following components: Wherein, by weight, the main resin includes: 5-35 parts of the first polymer Second polymer 0-25 parts 5-30 parts of the third polymer The first polymer includes one or more of styrene-ethylene-butadiene-styrene block copolymer (SEBS), styrene-ethylene / propylene-styrene block copolymer (SEPS), hydrogenated styrene isoprene diblock copolymer (SEP), styrene-polyisobutylene-styrene block copolymer (SIBS), and pressure-sensitive amorphous polyolefin (APAO); The second polymer includes one or more of butyl rubber (IIR), polyisobutylene (PIB), polyisoprene (LIR), and polybutadiene (LBR); a third polymer comprising one or more of styrene-butadiene-styrene block copolymer (SBS), styrene-isoprene-styrene block copolymer (SIS), and styrene-butadiene block copolymer (SBR); The contact enhancer comprises fumed silica loaded with UV326, the particle size of which is less than 25 μm, and the amount of UV326 accounts for 5-20% of the weight of the fumed silica, and comprises the following loading steps: (1) adding an aminosilane coupling agent to an organic dispersion of fumed silica to react and obtain a modified silica suspension; (2) Add UV326 and a catalyst to the suspension of step (1), and stir the reaction under nitrogen protection to obtain fumed silica loaded with UV326.

2. The transparent hot melt pressure sensitive adhesive according to claim 1, characterized in that: The hydrogenated petroleum resin includes one or more of hydrogenated C5 petroleum resin, hydrogenated C5-C9 copolymer petroleum resin, hydrogenated C9 petroleum resin, and styrene series monomer resin; The plasticizer comprises at least one of mineral oil and low molecular weight polyisobutylene; The antioxidant comprises at least one of antioxidant 1010 and antioxidant 168; The anti-aging agent includes at least one of an ultraviolet absorber and a light stabilizer.

3. The transparent hot melt pressure sensitive adhesive according to claim 2, characterized in that: The hydrogenated petroleum resin is a hydrogenated C5C9 copolymer petroleum resin, and the ring and ball softening point is greater than 80°C and less than 130°C; The plasticizer is naphthenic oil and / or polyisobutylene with a molecular weight lower than 1300; The ultraviolet absorber includes one or more of UV326, UV328, and UV-P; The light stabilizer is one or more of UV944 and UV622.

4. The transparent hot melt pressure-sensitive adhesive according to any one of claims 1 to 3, characterized in that: In parts by weight, the main resin includes: 10-30 parts of the first polymer 5-20 parts of the second polymer 10-25 parts of the third polymer, The first polymer is selected from at least one of styrene-ethylene-butadiene-styrene block copolymer (SEBS), styrene-ethylene / propylene-styrene block copolymer (SEPS), and pressure-sensitive amorphous polyolefin (APAO); Among them, styrene-ethylene-butadiene-styrene block copolymer (SEBS), styrene-ethylene / propylene-styrene block copolymer (SEPS), styrene content ≤ 30%, MI value > 5, 200 ° C, 5.0 kg; The cohesive strength of the pressure-sensitive amorphous polyolefin (APAO) is less than 2.5 MPa; the second polymer has no hard segment structure, and the weight average molecular weight Mw is between 100,000 and 1.5 million; The third polymer has a styrene content of ≤30%, a diblock content of ≥50%, and an MI value of >5, 200° C., 5.0 kg.

5. The hot melt pressure sensitive adhesive according to any one of claims 1 to 3, characterized in that: The third polymer is pre-blended and modified with the UV326-loaded fumed silica, comprising the following steps: Add the third polymer, maleic anhydride, and UV326-loaded fumed silica into a kneader or a screw extruder, and react at 140-160° C. for 1-2 hours to obtain a modified third polymer.

6. The hot melt pressure sensitive adhesive according to any one of claims 1 to 3, characterized in that: At least part of the first polymer grafted antioxidant 1010 comprises the following steps: (1) dissolving maleic anhydride in an organic solvent to obtain a reserve solution; adding the organic solvent, antioxidant 1010 and a catalyst into a reaction container, and stirring to obtain a uniform solution; (2) Under nitrogen protection, the solution temperature is lowered to -20°C to -5°C, and the reserve solution is dripped into the reaction container to react the antioxidant 1010 with maleic anhydride; (3) After the reaction is completed, the temperature of the mixed solution in the reaction container is raised to 0° C. to 15° C., and deionized water is added dropwise to the mixed solution for quenching; (4) separating the organic phase after standing, concentrating under reduced pressure, cooling to crystallize, filtering and drying to obtain a reactive antioxidant; (5) adding at least a portion of the first polymer to an internal mixer for melting, adding the reactive antioxidant, mixing for 5-10 minutes, and then adding the organic peroxide, mixing for 1-5 minutes to obtain the first polymer grafted with an antioxidant.

7. A method for preparing the UV-resistant, creep-resistant transparent hot-melt pressure-sensitive adhesive according to any one of claims 1 to 6, characterized in that: The steps include: S1, adding a first polymer, a hydrogenated petroleum resin, a plasticizer, an antioxidant and an optional second polymer into a preheated reaction device, and stirring them thoroughly to obtain a premix; S2. Add an anti-aging agent, a catalytic enhancer and a third polymer to the premix, stir thoroughly, and evacuate to obtain a transparent hot-melt pressure-sensitive adhesive product that is UV-resistant and creep-resistant.

8. Use of the UV-resistant, creep-resistant transparent hot-melt pressure-sensitive adhesive according to any one of claims 1 to 6 in optical fiber bonding.

Citation Information

Patent Citations

  • A transparent butyl hot melt sealant and its preparation method

    CN101805569B

  • A flame retardant transparent hot melt pressure sensitive adhesive and its preparation method and application

    CN117304869B

  • Flame-retardant hot-melt pressure-sensitive adhesive and preparation method and application thereof

    CN106221629A

  • Foamable hot-melt pressure-sensitive adhesive door waterproof film composite material and preparation method thereof

    CN107987743A

  • Hot-melt pressure-sensitive adhesive special for high-weather-resistance non-asphalt-based pre-laid waterproof roll and preparation method thereof

    CN110713809A